Indexing environmental sustainability literacy knowledge among malaysian youth: confirmatory factor analysis approach (cfa). Issue 1 (March 2021) - Norkhaidi, S B; Mahat, H; Hashim, M; Saleh, Y; Nayan, N
Abstract: An index is one of the approaches to measuring behaviour and is commonly used in economics and social sciences. Therefore, this study aimed to investigate the key factors for indexing environmental sustainability literacy knowledge among Malaysian youth using exploratory and confirmatory analyses. Respondents consisted of 100 Malaysian youth who were selected using a simple random sampling technique. A questionnaire using a Likert scale was used to get the responses. The results show that study items achieved acceptable reliability with Cronbach Alpha values for each variable greater than .70 and meet the test of normality. Then, the data obtained were processed through an exploratory factor analysis (EFA) to observe the factor structure of environmental sustainability literacy knowledge. Next, a confirmatory factor analysis (CFA) was also conducted to validate the accumulated variables. In conclusion, the findings from both analyses have identified and validated the four key factors in Malaysian youth environmental sustainability literacy knowledge, namely lithosphere, hydrosphere, atmosphere, and biosphere. The findings also indicate that a fit indices value is in compliance with the terms set forth. Therefore, the four factors set out should be emphasized in the construction of instruments for indexing environmental sustainability literacy knowledge among Malaysian youth.